Design of High-frequency Module for Cascaded Power Electronic Transformer - LUO Jianbo; FAN Wei; PENG Kai; LIU Huadong (Kongzhi Yu Xinxi Jishu)
Based on the principle analyses and comparison of the main circuit topologies of high voltage power electronic transformer(PET), a high-frequency module for high-voltage cascaded PET was proposed. Electrical design of the module was finished for its LLC gain characteristics and the necessary conditions to achieve ZVS. Accuracy of the circuit design parameters was verified by test and loss analysis was performed in the DC-DC side of the high-frequency module based on IGBT switching process. The efficiency of the DCDC converter is improved due to no loss of its turn-on process.